Impedimetric Sensor for Pentoses Based on Electrodeposited Carbon Nanotubes and Molecularly Imprinted poly-o-phenylenediamine - Sousa, Miguel S. P. [UNESP] (2020)
Impedimetric D-Xylose and D-Arabinose sensors was development from composite electrodes of graphite and histological paraffin, modified with functionalized multi-walled carbon nanotubes (FMWCNTs) based on molecular imprinted poly-o-phenylenediamine (poly-o-PD). The contribution of this work was not only the development of a D-xylose and D-Arabinose MIP impedimetric sensor with good performance, but also the electrodeposition method for FMWCNTs onto surface of graphite composites electrodes with ease of control and reproducibility of the electrodeposition process. The sensors were characterized by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), field emission gun scanning electron microscopy (FEG-SEM) and RAMAN spectroscopy. The MIPs sensors for the pentoses have good selectivity, sensitivity in the concentration range of 1.0 x 10(-11) to 1.0 x 10(-10) mol 1(-1) with limit of detection (LOD) of 4.50 x 10(-12) mol 1(-1) for D-Xylose and 4.25 x 10(-12) mol 1(-1) for D-Arabinose. MIPs was applied to determination of pentoses in samples of sugarcane bagasse hydrolysates using the standard addition method and validated by recovery study, which presented satisfactory results between 92.9% and 115.5%. (C) 2020 The Electrochemical Society (ECS). Published on behalf of ECS by IOP Publishing Limited.